Green Fabrication of Cu2O@BSA Nanoparticles, Characterization and Formation Mechanism. Issue 1 (24th July 2021) - Yang, Ailing; Dai, Zhikuang
Abstract: A green method was used to synthesize Cu2 O@BSA nanoparticles (NPs). The influential factors on the morphologies of NPs were investigated. The result showed that the alkalinity of reactant solution plays an important role. Fourier transform infrared (FTIR) spectroscopy indicated that Cu 2+ interacts strongly with O positioned at peptide chain and N in amide of BSA. The formation mechanism of Cu2 O@BSA NPs depends on the unfolding of the peptide of BSA proceeds the electrostatic interaction between Cu 2+ and BSA. The experimental results are of importance for fabrication of semiconductor NPs by using BSA or other protein as coating agents.